Institutional Investment in Infrastructure in Developing Countries : Introduction to Potential Models - Inderst, Georg; Stewart, Fiona (World Bank, Washington, DC, 2014)
The link between infrastructure and economic growth is widely acknowledged -- as is the infrastructure gap, which can act as a break on growth in emerging markets and developing economies (EMDEs). Since the global economic and financial crisis, the challenges of raising financing for infrastructure projects in EMDEs are also well known. The challenges come from stretched government finances and restrictions on global bank lending. Hence much attention has been focused on the potential for institutional investors as a growing potential source of financing. This paper argues that infrastructure projects can potentially deliver long-term returns, but investments, particularly in EMDEs need to be carefully structured to meet the needs of both sides. The paper first considers the existing types of institutional investors and their potential for filling the infrastructure financing gap. The challenges of adjusting asset allocations, particularly toward EMDE infrastructure, are discussed and examples of projects where institutional investors have been involved are given. Finally, the paper considers a range of models for the involvement of institutional investors in EMDEs and makes initial proposals for how to determine which model fits best in a particular country context.